ESG disclosure, green innovation, and corporate performance: empirical evidence from listed Chinese a-share companies - Zhang, Xiaoyuan; Wang, Shenglian; Raja Ahmad, Raja Azdrin; Azmi, Nurul Azlin (UiTM Cawangan Johor, 2024)
In recent years, the ESG concept has been highly aligned with China's sustainable development strategy and green and low-carbon transition goals. ESG disclosure and green innovation have become a hot issue for shareholders, governments and investors. This study examines the relationship between ESG, green innovation and performance. This paper uses Chinese A-share listed companies in the software and information technology service industry from 2015 to 2022 as research samples to investigate the impact of ESG disclosure and green innovation on corporate performance. Using panel fixed effect regression, this study found that ESG disclosure and green innovation can significantly improve corporate performance. Furthermore, ESG disclosure and green innovation are complementary in promoting corporate performance. The finding of this study incentivizes corporates to invest in ESG disclosure and green innovation to pursue sustainable performance. This study only uses a sample of a single industry, so the conclusions of this study do not have explanatory power for corporates in other industries.